2021
DOI: 10.1097/scs.0000000000007645
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three-Dimensional Heads up Ophthalmic Surgery Demonstration From the Perspective of Surgeons and Postgraduate Trainees

Abstract: Background: To evaluate the satisfaction of surgeons and trainees with three-dimensional (3D) ophthalmic surgery during a demonstration compared to traditional surgery Methods: This validated questionnaire-based study was conducted over 1-month during which Ngenuity 3D surgery was demonstrated. All surgeons and trainees exposed were recruited to complete a questionnaire comprising visualization, physical, ease of use, teaching and learning, and overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Although not specifically analyzed in the present study, the authors confirm previous reports of substantial ergonomic benefits of 3D visualization for surgeons [10,11], advantages in real time, in-theater simultaneous viewing of the surgery by other surgeons and/or staff, expanding the possibilities with regard to training, and didactic purposes [11][12][13][14]. The learning curve was very short, as, in the present case, there was no training for the authors prior to this study.…”
Section: Discussionsupporting
confidence: 86%
“…Although not specifically analyzed in the present study, the authors confirm previous reports of substantial ergonomic benefits of 3D visualization for surgeons [10,11], advantages in real time, in-theater simultaneous viewing of the surgery by other surgeons and/or staff, expanding the possibilities with regard to training, and didactic purposes [11][12][13][14]. The learning curve was very short, as, in the present case, there was no training for the authors prior to this study.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, a questionnaire-based study that assessed the satisfaction levels of surgeons and trainees with 3D HUD compared to the traditional microscope found that both surgeons and trainees were more satisfied with 3D surgery. 38 Notably, the trainees reported better satisfaction levels with 3D in various subcomponents, such as visualization, physical aspects, ease of use, and education. 38…”
Section: Broader Advantages Impact On Medical Educationmentioning
confidence: 88%
“…38 Notably, the trainees reported better satisfaction levels with 3D in various subcomponents, such as visualization, physical aspects, ease of use, and education. 38…”
Section: Broader Advantages Impact On Medical Educationmentioning
confidence: 88%
“…It is increasingly used by ophthalmologists in the last two decades and enhances visualization of surgical elds by projecting the view to a 3D monitor 5,6 . 3D HUDS-based ophthalmic surgery is reported to offer several advantages: better ergonomics for surgeons, enhanced depth perception and visualization of peripheral surgical eld, reduced phototoxicity, and improved teaching opportunities [7][8][9][10][11][12][13] . 3D HUDS offer similar safety and e ciency as the traditional binocular microscope 8, 14,15 .…”
Section: Introductionmentioning
confidence: 99%